Neural Measures of Conscious and Unconscious Memory - Ken A. Paller (Behavioural Neurology)
Neuropsychological studies of memory disorders have played a prominent role in the development of theories of memory. To test and refine such theories in future, it will be advantageous to include research that utilizes physiological measures of the neural events responsible for memory. Measures of the electrical activity of the brain in the form of event-related potentials (ERPs) provide one source of such information. Recent results suggest that these real-time measures reflect relevant encoding and retrieval operations. In particular, distinct electrical responses have been associated with recollective processing of words and with priming of visual word-form. This source of evidence can thus enrich our understanding of both the cognitive structure and neural substrates of human memory.